The Role of Islamic Boarding Schools in Enhancing Educational Quality and Students’ Learning Motivation: A Case Study at Pondok Pesantren Darussalamah Braja Dewa, East Lampung - Andika Suryanto; Ayu Irmasari; Erna Armiyati (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2020)
The proliferation of Islamic educational institutions in Indonesia highlights the strategic role of pesantren (Islamic boarding schools) in shaping educational quality and fostering students’ motivation to learn. This study explores how Pondok Pesantren Darussalamah Braja Dewa contributes to improving educational standards and cultivating santri learning enthusiasm through formal, non-formal, and informal learning systems. Employing a qualitative research approach, data were collected through interviews, observation, and documentation involving the management and students of the pesantren. The results reveal that the institution enhances educational quality by systematically organizing learning objectives, subject standards, annual and semester programs, daily learning schedules, and extracurricular activities. In parallel, the pesantren promotes learning motivation through character-building practices, religious habituation, social mentoring, emotional and spiritual intelligence development, and vocational training. Educational strategies such as wetonan, sorogan, halaqah, and musyawarah also play a vital role in achieving these outcomes. Furthermore, the pesantren functions as a religious, social, and leadership training center, supporting students in becoming intellectually grounded and spiritually responsible individuals. These findings underscore the continuing relevance and adaptability of pesantren in the modern educational landscape.